Pemanfaatan Pocket Park Sebagai Infrastruktur Hijau di Permukiman Islami (Studi Kasus: Kampung Arab, Kota Malang) - Senjana, Suci; Junara, Nunik; Mutiara, Elok (Universitas Diponegoro, Indonesia, 2021)
Urban areas have the character of increasingly dense buildings and less land that can be used for green infrastructure. So that the option to increase green open space is increasingly difficult. Along with the population growth in Kampung Arab and the low number of public facilities, the environment became very crowded and have less adequate public open spaces for the residents who lived here. Kampung Arab itself is a settlement dominated by Muslim residents who have been in this area for a long time. This study aims to analyze the feasibility of applying the pocket garden concept to Islamic residential kasawan which is currently in a congested condition. The first step is to collect data from observations, surveys and literature selection. Then, the method used to analyze is discourse analysis and selective criteria. These two processes show the results in the form of the benefits of the pocket garden concept in settlements, a map of the location at a point in Kampung Arab which can be used as a pocket garden and a map of the distance from the pocket garden to the surrounding house. These findings explain that the concept of green open space for narrow land can improve the quality of life for urban communities, especially those in Kampung Arab. Therefore, the application of the concept as a concept that is suitable for use in the future both in planning and designing in Kampung Arab, urban areas of the population. There are related professions that can work using this system such as spatial policy makers, planners, and architects.